2014
DOI: 10.1063/1.4892880
|View full text |Cite
|
Sign up to set email alerts
|

Infrared luminescence for real time ionizing radiation detection

Abstract: Radio-luminescence (RL) optical fiber sensors enable a remote, punctual, and real time detection of ionizing radiation. However, the employment of such systems for monitoring extended radiation fields with energies above the Cerenkov threshold is still challenging, since a spurious luminescence, namely, the “stem effect,” is also generated in the passive fiber portion exposed to radiation. Here, we present experimental measurements on Yb-doped silica optical fibers irradiated with photon fields of different en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…First, a wide variety of scintillator materials emit in the red wavelength region, i.e., 600–750 nm (Jordan 1996, Molina et al 2012, Veronese et al 2014, McCarthy et al 2013, Teichmann et al 2013, Martinez et al 2015). Scintillation in longer wavelengths is advantageous for dosimetry because it greatly simplifies the removal of the most important sources of measurement uncertainty for scintillation detectors—the Cerenkov and fluorescence effects (Beddar et al 1992a, Therriault-Proulx et al 2013a), which exhibit a continuous emission spectrum most prominent in the blue region.…”
Section: Introductionmentioning
confidence: 99%
“…First, a wide variety of scintillator materials emit in the red wavelength region, i.e., 600–750 nm (Jordan 1996, Molina et al 2012, Veronese et al 2014, McCarthy et al 2013, Teichmann et al 2013, Martinez et al 2015). Scintillation in longer wavelengths is advantageous for dosimetry because it greatly simplifies the removal of the most important sources of measurement uncertainty for scintillation detectors—the Cerenkov and fluorescence effects (Beddar et al 1992a, Therriault-Proulx et al 2013a), which exhibit a continuous emission spectrum most prominent in the blue region.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is clear that the attractiveness of fiber optic dosimeters would be greatly enhanced by employing a scintillation signal free from any spectral superposition with the spurious ones. We demonstrated that it is possible using a scintillator with an emission in the near infrared, that can be clearly distinguished from the stem effect emission occurring in the UV-VIS spectral region 25,26) . This work aims to summarize the main findings of a recent comprehensive characterization of the dosimetric properties of Yb-doped silica optical fibers coupled with an optical detector prototype based on an avalanche photo-diode (APD) 27) .…”
Section: Doped Portionmentioning
confidence: 99%
“…Finally, the luminescence and dosimetric properties of Yb-doped silica optical fibres are currently being studied. The sharp RL emission line at 975 nm due to the 2 F 5/2 -2 F 7/2 transition of Yb 3+ makes this dopant very promising for a prompt and efficient subtraction of the stem effect contribution simply by optical filtering [39].…”
Section: Doped Silica Optical Fibre Based Dosimetersmentioning
confidence: 99%
“…Recently, our research has been addressing the use of dopants emitting in the red and IR region of the visible spectrum in order to implement alternative methods for removing the stem effect contribution on the basis of the analysis of the RL spectra or optical filtering [36][37][38][39]. For this purpose, Eu-and Yb-doped silica fibres were produced and a thermoelectric cooled back-thinned CCD array spectrometer (Prime X, B&W Tek Inc., USA) operating within a wavelength range 200-990 nm was used as optical detector.…”
Section: Doped Silica Optical Fibre Based Dosimetersmentioning
confidence: 99%